MANUFACTURE OF INDOOR 3D SCANNER PROTOTYPE USING LASER RANGEFINDER - Ghilman Oemar, M
3D Scanner instruments are standard tools in survey and mapping, yet devices specialized for indoor scanning are rare. Existing scanners usually use photogrammetry and structured-light scanning method which is less accurate because it is sensitive to light from environment. This research makes 3D scanner protoype using laser rangefinder that are more accurate because of the laser’s directional, high-brightness, and monochromatic properties, make the scanner unaffected by environmental light. The prototype made is divided into two, hardware consists of laser rangefinder that driven by motor steppers. Its movement in horizontal axis is 360° ( one full rotation) while in vertical axis is only 255°, due to the protoype’s mounting. Beside hardware systems, there is software that controls motor stepper’s rotation and reconstruct the distance measurement’s result into point clouds in cartesian coordinates that represent the profile of scanned area. The maximum number of points that can be scanned is 80,000 points with the horizontal and vertical smallest angle is 0.9°. The prototype has an accuracy rate of 5.14%.